Strategy for Water Management in Palestine - Palestinian Water Authority (Ramallah Palestinian Water Authority, 1998)
Summary -- The overall development objectives of the Water Management Strategy is to translate the messages from the National Water Policy into strategic imperatives. The strategy emphasizes the necessary aspects of water development such as the establishment of a comprehensive framework for sustainable management of Palestine's water resources.In addition to the development of appropriate institutional set-up for reforming and strengthening the water sector in co-ordination with the relevant stakeholders, this long term and co-ordinate strategy for the water sector will be used as an overall basis for the further planning of the activities and tasks in the water sector. The main challenge facing the Palestinians in implementing this strategy is to achieve sovereignty and full control over their water resources. It is most urgent to resolve the Palestinians water right issue, which comprises securing comprehensive control and management of their water resources, including the ground and surface water totally originating inside the West Bank and Gaza Strip Governorates; in addition to their riparian rights in the Jordan River Basin and Gaza Wadis. The Control over the water resources is the basis for the development and management of these water resources in order to meet the needs for water essential for further economic development. The overall objective for Palestine in the water sector to secure an environmentally sound and sustainable development of the water through efficient and equitable water management. The multi-objective water resources management strategy builds upon the eight key elements which intend to meet this objective and all the challenges in the water sector.
1. Background -- 2. Challenges and Opportunities -- 3. National Water Policy -- 4. Key Elements of the water management strategy -- 5. Scope of work and objectives -- 6. Implantation of the strategy --
Keywords: Natural resources; WATER; WATER MANAGEMENT; STRATEGY; PALESTINE